Uncovering a missing demographic in trauma registries: epidemiology of trauma among American Indians and Alaska Natives in Washington State. Issue 5 (29th April 2015) - Hoopes, Megan J; Dankovchik, Jenine; Weiser, Thomas; Cheng, Tabitha; Bigback, Kristyn; Knaster, Elizabeth S; Sugerman, David E
Abstract : Background: The objectives of this study were to evaluate racial misclassification in a statewide trauma registry and to describe the epidemiology of trauma among the Washington American Indian and Alaska Native (AI/AN) population. Methods: We performed probabilistic record linkage between the Washington Trauma Registry (2005–2009) and Northwest Tribal Registry, a dataset of known AI/AN. AI/AN patients were compared with caucasians on demographic, injury and clinical outcome factors. A multivariable model estimated odds of mortality. Results: Record linkage increased ascertainment of AI/AN cases in the trauma registry 71%, from 1777 to 3039 cases. Compared with caucasians, AI/AN trauma patients were younger (mean age=36 vs 47 years, p<0.001) and more commonly male (66.5% vs 61.2%, p<0.001). AI/AN experienced more intentional injuries (suicide or homicide: 20.1% vs 6.7%, p<0.001), a higher proportion of severe traumatic brain injury (20.7% vs 16.8%, p=0.004) and were less likely than caucasians to use safety equipment such as seat belts/airbags (53.9% vs 76.7%, p<0.001). ISSs were similar (ISS >15: 21.4% vs 20.5%, p=0.63), and no difference was observed in mortality after adjustment for covariates (p=0.58). Conclusions: Linkage to a state trauma registry improved data quality by correcting racial misclassification, allowing for a comprehensive description of injury patterns for the AI/AN population. AI/AN sustained more severe injuries with similar postinjury outcomes to caucasians. Future efforts should focus on primary prevention for this population, including increased use of seat belts and child safety seats and reduction of interpersonal violence and suicide.